Experimental analysis of steering wheel vibrations of an agriculture tractor for reduction of hand-arm vibrations. (June 2022) - Naygaonkar, Sumit Someshwar; Desai, Sandeep Rangrao
Steering wheel vibration is one of the most important factors in determining the operator comfort in agricultural tractors. It is important to investigate steering wheel vibrations in an agricultural tractor in order to improve the operator's comfort and decrease the negative health impacts on the operator's hand. The Mahindra 575 DI tractor was selected for further investigation and development as the maximum vibration acceleration was found in the Mahindra 575 DI tractor while measuring the amplitude of vibration on various tractors. The experimental test setup was designed with a solution to reduce steering wheel vibrations. The experimental analysis of steering wheel vibration of an agriculture tractor for the reduction of Hand-Arm Vibration Syndrome (HAVS) is presented in this research article. The vibration level was decreased effectively after establishing a tuned mass damper between the steering gearbox and the vibration exciter.